Identificación de las zonas de riesgo ofídico en Córdoba, Argentina, mediante el programa SIGEpi. - Leynaud, Gerardo C.; Reati, Gustavo J. (Pan American Journal of Public Health / Revista Panamericana de Salud Pública, 2009)
Objectives. To determine the case distribution of accidental ophidism in the Córdoba province of Argentina, identify high risk areas, and evaluate the usefulness of the SIGEpi software program (Pan American Health Organization, Washington, DC, United States of America). Methods. Information regarding the 299 cases of accidental ophidism reported in Córdoba in 1995-2006 was collected from the Provincial Epidemiology Department's official records of incidents involving venomous creatures. The SIGEpi software program was used for geographic mapping. Specific maps were produced to identify, quantify, and visualize the danger zones and areas of high risk for ophidism. Results. The incidents occurred mostly in the northern and western areas of the province. Snakes of the Bothrops genus were responsible for the majority of the incidents (87.7% of the total). The departments with the highest annual incidence rates were Pocho and Río Seco ( > 10 incidents per 100 000 residents). Three ophidism high-risk zones were identified: one in far west of the province, another in the far north, and another just north of Bañados del Río Dulce and the Mar Chiquita lagoon. Conclusions. Accidental ophidism constitutes a major health problem in the Córdoba province where incidence rates are higher than those areas with more severe economic issues tied to rural labor. SIGEpi software is a reasonable choice for studying public health challenges and proved to be effective in identifying areas at high risk for ophidism.